Transcriptome analysis of microRNAs, circRNAs, and mRNAs in the dorsal root ganglia of paclitaxel-induced mice with neuropathic pain - Mao, Qingxiang; Tian, Lixia; Wei, Jianxiong; Zhou, Xiaoqiong; Cheng, Hong; Zhu, Xuan; Li, Xiang; Gao, Zihao; Zhang, Xi; Liang, Lingli (Frontiers in Molecular Neuroscience, 2022)
The microtubule-stabilizing drug paclitaxel (PTX) is a chemotherapeutic agent widely prescribed for the treatment of various tumor types. The main adverse effect of PTX-mediated therapy is chemotherapy-induced peripheral neuropathy (CIPN) and neuropathic pain, which are similar to the adverse effects associated with other chemotherapeutic agents. Dorsal root ganglia (DRG) contain primary sensory neurons; any damage to these neurons or their axons may lead to neuropathic pain. To gain molecular and neurobiological insights into the peripheral sensory system under conditions of PTX-induced neuropathic pain, we used transcriptomic analysis to profile mRNA and noncoding RNA expression in the DRGs of adult male C57BL/6 mice treated using PTX. RNA sequencing and in-depth gene expression analysis were used to analyze the expression levels of 67228 genes. We identified 372 differentially expressed genes (DEGs) in the DRGs of vehicle- and PTX-treated mice. Among the 372 DEGs, there were 8 mRNAs, 3 long non-coding RNAs (lncRNAs), 16 circular RNAs (circRNAs), and 345 microRNAs (miRNAs). Moreover, the changes in the expression levels of several miRNAs and circRNAs induced by PTX have been confirmed using the quantitative polymerase chain reaction method. In addition, we compared the expression levels of differentially expressed miRNAs and mRNA in the DRGs of mice with PTX-induced neuropathic pain against those evaluated in other models of neuropathic pain induced by other chemotherapeutic agents, nerve injury, or diabetes. There are dozens of shared differentially expressed miRNAs between PTX and diabetes, but only a few shared miRNAs between PTX and nerve injury. Meanwhile, there is no shared differentially expressed mRNA between PTX and nerve injury. In conclusion, herein, we show that treatment with PTX induced numerous changes in miRNA expression in DRGs. Comparison with other neuropathic pain models indicates that DEGs in DRGs vary greatly among different models of neuropathic pain.